A case of rheumatoid spondyloarthritis! - Sujatha N; Balameena S (Journal of Medical and Scientific Research, 2019)
Coexistence of rheumatoid arthritis and spondyloarthritis in one patient is rare. Here we report a 42-year-old male with symmetrical small and large joint arthritis of upper and lower limbs, bilateral sacroilitis without clinical evidence of psoriasis or inflammatory bowel disease. He had high titres of both rheumatoid factor (RF) (125.5IU/ml) and anti-citrullinated peptide antibodies (ACPA) (>200U/mL) with human leukocyte antigen (HLA) typing revealing positivity for both HLA B27 and HLA DR4. Patient was managed with steroids, analgesics, Disease-modifying anti-rheumatic drugs (DMARDs) and biologicals. Our patient’s initial clinical presentation and serology were suggestive of Rheumatoid arthritis but later he developed features of spondyloarthritis. Though he had genetic predisposition to both the diseases, clinical features and imaging studies on follow up were more in favour of spondyloarthritis. It is unclear as to whether the small joint arthritis of hands could be attributed to rheumatoid arthritis or spondyloarthritis. It is possible that these two conditions probably occur by chance or this could constitute an overlap syndrome between the two rheumatic conditions. Such cases pose difficulties in diagnosis and further study of such patients may help in early diagnosis and effective intervention.